El café como potencial turístico del Cantón Olmedo, provincia de Loja - Guillin Guillin, Vanessa Alexandra (2023)
Olmedo coffee is recognized nationally and internationally for its quality, aroma, flavor and production. Therefore, the present work called “Coffee as a tourist potential of the Olmedo canton, province of Loja”, has as a general objective, to identify the gastronomic potential of coffee for the tourist development of the canton, likewise, two specific objectives were raised: the diagnosis of the product “the coffee” in the Olmedo canton, for this the Carla Ricaurte community information gathering methodology was used, observation techniques, surveys and interviews were used to complete the demand form, MINTUR summary form, a PESTEL analysis and the INPC adapted sheet. For the second specific objective: Establish tourism development alternatives based on the element studied, a SWOT matrix was used and then a crossed SWOT to determine the strategies. The results were that Olmedo has tourist and complementary services, the surveys were carried out at the EAP of the Olmedo canton and its area of influence to know the potential demand, two producers and merchants were interviewed to find out their opinion about coffee and complete the demand sheet, with the information gathering sheets of the MINTUR attractions, 10 tourist attractions of hierarchy II were determined, the sheet adapted from the INPC was used to know the process developed by coffee growers and the PESTEL technique for an external analysis. With the SWOT, the threats and potential that Olmedo coffee has were obtained, and the crossed SWOT helped define the strategies. It is concluded that the Olmedo canton has the potential to develop tourism and a tourist product based on coffee and 5 strategies were taken into account to potentialize Olmedo coffee for tourism.